Goal Salience Affects Infants’ Goal-Directed Gaze Shifts - Henrichs, Ivanina; Elsner, Claudia; Elsner, Birgit; Gredebäck, Gustaf (Frontiers in Psychology, 2012)
Around their first year of life, infants are able to anticipate the goal of others’ ongoing actions. For instance, 12-month-olds anticipate the goal of everyday feeding actions and manual actions such as reaching and grasping. However, little is known whether the salience of the goal influences infants’ online assessment of others’ actions. The aim of the current eye-tracking study was to elucidate infants’ ability to anticipate reaching actions depending on the visual salience of the goal object. In Experiment 1, 12-month-old infants’ goal-directed gaze shifts were recorded as they observed a hand reaching for and grasping either a large (high-salience condition) or a small (low-salience condition) goal object. Infants exhibited predictive gaze shifts significantly earlier when the observed hand reached for the large goal object compared to when it reached for the small goal object. In addition, findings revealed rapid learning over the course of trials in the high-salience condition and no learning in the low-salience condition. Experiment 2 demonstrated that the results could not be simply attributed to the different grip aperture of the hand used when reaching for small and large objects. Together, our data indicate that by the end of their first year of life, infants rely on information about the goal salience to make inferences about the action goal.